X-ray Diffraction Study of Intermetallic Cu-Al Interconnection in Electronic Components - Thangaraj, Joseph Sahaya Anand; Chua, Kok Yau; Hng, May Ting; Lee, Cher Chia (2012)
Cu wire bonding has been an emerging interconnection technique for semiconductor industry. Research of intermetallic compounds (IMCs) of Cu (wire) – Al (bond pad metallization) in nanometer scale at the bonding interface is usually carried out with expensive and time consuming analytical techniques. X-ray Diffraction is a potential tool that offers easier sample preparation, lower cost of analysis and high accuracy. This paper attempts to utilize X-ray Diffraction tool to study the nano-size IMC that present at the Cu-Al interface. Various sample preparation methods are applied prior to XRD measurement. Effectiveness of each preparation methods towards the detection of IMC is examined.